2020
DOI: 10.1155/2020/5181587
|View full text |Cite
|
Sign up to set email alerts
|

Oral Chinese Herbal Medicine as Prophylactic Treatment for Episodic Migraine in Adults: A Systematic Review and Meta‐Analysis of Randomized Controlled Trials

Abstract: Background. The prophylactic effects of Chinese herbal medicine (CHM) for migraine were examined in numerous clinical trials. This review aimed to analyze the effectiveness and safety of CHM as prophylactic treatment of migraine compared to flunarizine. Methods. Nine databases were searched for randomized controlled trials (RCTs) that evaluated effects of CHM for episodic migraine prophylaxis compared to flunarizine, published before March 2019. Results. Thirty-five RCTs with 2,840 participants met the inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 53 publications
5
27
0
Order By: Relevance
“…Chuan xiong was the most popular used herb for migraine among the included RCTs, this is consistent with the findings of previous studies (14,(55)(56)(57). In addition, we found that chuan xiong and bai zhi and chuan xiong and dang gui were the two mostly used herb pairs for migraine management.…”
Section: Mechanism Of Core Herbs For Migrainesupporting
confidence: 92%
See 2 more Smart Citations
“…Chuan xiong was the most popular used herb for migraine among the included RCTs, this is consistent with the findings of previous studies (14,(55)(56)(57). In addition, we found that chuan xiong and bai zhi and chuan xiong and dang gui were the two mostly used herb pairs for migraine management.…”
Section: Mechanism Of Core Herbs For Migrainesupporting
confidence: 92%
“…As a commonly used complementary therapy for migraine management in China (12), the benefits, safety, and economic cost induced by CHM remain in heated debates (12). Although the efficacy and effectiveness of CHM for migraine were supported by previous research (13)(14)(15)(16)(17), it remains inconclusive in terms of whether CHM should be used solely or in combination with conventional pharmacotherapies for migraine in real-world clinical practice, due to the low quality of the above evidence. In addition, it is widely recognized that preventive treatments should take patients' preferences, proven efficacy, and drug side effects into consideration in migraine management (18), which is consistent with the concept of evidence-based practice (64).…”
Section: Implication In Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Chinese herbal medicine (CHM), which is often prescribed to migraine patients in China [25], has gained clinical research evidence as an effective alternative or complementary therapy for migraine in recent years. However, most of the existing evidence has been generated from randomised controlled trials (RCTs) [26][27][28][29][30] and RCT-based systematic reviews [31][32][33][34]. Under controlled settings, RCTs usually apply strict selection criteria and provide unified treatments to all participants [35].…”
Section: Introductionmentioning
confidence: 99%
“…The diversity of pathologies covered by the remaining articles is considerable, with three articles related to cancer (involving 54, 14 and 18 RCTs)[33][34][35], three related to hypertension (involving 30, 17 and 39 RCTs)[36][37][38], three related to COVID-19 (involving 19, 7 and 18 RCTs)[39][40][41], two related to depression (involving 40 and 16 RCTs)[42,43], two related to headache (involving 31 and 30 RCTs)[44,45], and the others related to allergic rhinitis (involving 17 RCTs)[46], spinal cord injury (involving 26 RCTs)…”
mentioning
confidence: 99%